Quantitative Determination of Heavy Metal Contamination in Horse Mackerel and Whiting Caught in the Sea of Marmara - CÜCÜ, AYŞEN; ERDOĞAN, GÜLBİN (SPRINGER, 2019)
In this study, the concentrations of lead, cadmium and manganese were determined in horse mackerel (Trachurus mediterraneus) and whiting (Merlangius merlangus euxinus) that were caught in the Sea of Marmara. These are commonly consumed fish species in this region. Fish were provided by a fishermen quarterly between March 2013 and December 2013 and, separated according to size (small, medium and large). Pb(II), Cd(II) and Mn(II) levels were determined using the wet digestion method by Graphite furnace atomic atomic absorption spectrophotometer. According to this study, for horse mackerel, the highest concentration of lead, cadmium, and manganese was 6.69 A mu g kg(-1) (September), 5.24 A mu g kg(-1) (March) and 9.24 A mu g kg(-1) (June), respectively. For whiting, the highest concentration of lead, cadmium, and manganese was 2.25 A mu g kg(-1) (June), 0.263 A mu g kg(-1) (September) and 10.4 A mu g kg(-1) (June), respectively. These heavy metal levels in fish were found to be acceptable for human consumption according to World Health Organization border values.
Keywords: Heavy metals; Graphite furnace atomic absorption spectrophotometry (GFAAS); Fish; Horse mackerel; Whiting; Marmara Sea; RISK-ASSESSMENT; FISH; TISSUES; RIVER; RESERVOIR; COAST; GULF; LEAD; DAM